Peningkatan Hasil Belajar IPS Menggunakan Model Mind Mapping Pada Siswa Sekolah Dasar - Astuti, Puji (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This research is motivated by the low social studies (IPS) learning outcomes among elementary school students caused by conventional learning processes that tend to be monotonous and teacher-centered. The primary focus of this study is to describe the improvement of social studies learning outcomes by implementing the Mind Mapping cooperative learning model. The research method employed is classroom action research with a descriptive qualitative and quantitative approach. The results indicate that the use of the Mind Mapping model effectively transforms the learning atmosphere to be more creative, cheerful, and enjoyable. Through the use of colors, curved lines, symbols, and images, students are able to absorb and retrieve information from the brain more naturally compared to traditional rote learning methods. The findings reveal a shift in learning patterns from teacher-centered to active learning, where students become more confident in presenting their ideas and possess a strong